2014
DOI: 10.1007/s00701-013-1991-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological findings in long-term intracranial pressure monitoring

Abstract: Infectious as well as haemorrhagic complication rates are well comparable with the common literature. The long-term implantation of an ICP probe does not seem to increase the risk of wound infections or brain abscess formation. Surprisingly, very high numbers of oedematous reactions after insertion of the intraparenchymal ICP monitor were seen. Reasons therefore could only be speculated upon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
0
29
0
4
Order By: Relevance
“…So far, telemetric ICP monitoring has been applied only in severe adult TBI (37). In previous investigations (38,39), complication rates were similar to those of cabled ICP sensors (40)(41)(42). Another telemetric device (Miethke/Aesculap Sensor Reservoir) has also been developed to measure ICP through an implanted ventricular shunt system (43,44).…”
Section: Measurement Of Icp Using a Parenchymal Icp Sensormentioning
confidence: 96%
“…So far, telemetric ICP monitoring has been applied only in severe adult TBI (37). In previous investigations (38,39), complication rates were similar to those of cabled ICP sensors (40)(41)(42). Another telemetric device (Miethke/Aesculap Sensor Reservoir) has also been developed to measure ICP through an implanted ventricular shunt system (43,44).…”
Section: Measurement Of Icp Using a Parenchymal Icp Sensormentioning
confidence: 96%
“…Antes at al, registered a technical error rate of the sensor reservoir ® of 8 % [8]. Several authors found error rates between 3 and 16 % for the parenchymatous ICP probes [1,2,8,19,20].…”
Section: Management Of Telemetric Devicesmentioning
confidence: 97%
“…NEUROVENT ® -P-tel probe has been proven to be safe and effective in telemetric ICP monitoring and is used as reference in acute therapy of elevated ICP as well as for the diagnosis of neurological diseases such as pseudotumor cerebri and idiopathic normal pressure hydrocephalus (iNPH)[1,2,4,5,8,10,11].The sensor reservoir ® (Miethke, Aesculap, Germany) is available to determine pressure conditions continuously within a shunt system and thus to assess over-or under-drainage during shunt therapy. Radiation exposure of CT scan or long and expensive MRI for the diagnosis of over-or under-drainage symptoms can thus be avoided.…”
mentioning
confidence: 99%
“…Tschan et al described a new technique for long-term home telemetric ICP monitoring by receiving the home telemonitoring data from the patients online as well as using Internet consultations. Since the introduction of the Raumedic Helmbrecht p-Tel device in 2009, there were several descriptions of domestic use [1,3]. This study, however, presents for the first time a detailed description of a bigger cohort, namely 20 patients using home telemetric ICP monitoring.…”
mentioning
confidence: 96%
“…The advantage of telemetric ICP monitoring in comparison with conventional ICP monitoring, besides a lower infection rate due to the closed system used, is the possibility to record the ICP within greater time intervals, at any time and for longer periods [1][2][3][4][5][6][7][8]12].…”
mentioning
confidence: 99%